The nature of the Cygnus extreme B supergiant 2MASS J20395358+4222505. Issue 3 (22nd February 2022) - Herrero, A; Berlanas, S R; Gil de Paz, A; Comerón, F; Puls, J; Ramírez Alegría, S; Garcia, M; Lennon, D J; Najarro, F; Simón-Díaz, S; Urbaneja, M A; Gallego, J; et al.
ABSTRACT: 2MASS J20395358+4222505  is an obscured early B supergiant near the massive OB star association Cygnus OB2. Despite its bright infrared magnitude ( K s = 5.82) it has remained largely ignored because of its dim optical magnitude ( B = 16.63, V  = 13.68). In a previous paper, we classified it as a highly reddened, potentially extremely luminous, early B-type supergiant. We obtained its spectrum in the U,   B and R spectral bands during commissioning observations with the instrument MEGARA at the Gran Telescopio CANARIAS. It displays a particularly strong Hα emission for its spectral type, B1 Ia. The star seems to be in an intermediate phase between supergiant and hypergiant, a group that it will probably join in the near (astronomical) future. We observe a radial velocity difference between individual observations and determine the stellar parameters, obtaining T eff  = 24 000 K and log  gc  = 2.88 ± 0.15. The rotational velocity found is large for a B supergiant, $v$  sin  i  = 110 ± 25 $\rm km\, s^{-1}$ . The abundance pattern is consistent with solar, with a mild C  underabundance (based on a single line). Assuming that J20395358+4222505  is at the distance of Cyg OB2, we derive the radius from infrared photometry, finding R  = 41.2 ± 4.0 R⊙, log( L /L⊙ ) = 5.71 ± 0.04 and a spectroscopic mass of 46.5 ± 15.0 M⊙ . The clumped mass-loss rate (clumping factor 10) is very high for the spectral type, $\dot{M}$  = 2.4 × 10 −6 M⊙ a −1 . The high rotational velocity and mass-loss rate place the star at the hot side of the bi-stability jump. Together with the nearly solar CNO abundance pattern, they may also point to evolution in a binary system, J20395358+4222505  being the initial secondary.